The clinical effects of Gyejibongnyeong-Hwan (Gui Zhi Fu Ling Wan) on patients with hyperlipidemia: A study protocol for a multicenter, double-blind, two-armed parallel, investigator-initiated, exploratory randomized controlled trial. Issue 16 (21st April 2023) - Ko, Mi Mi; Kim, Pyung-Wha; Jung, So Young; Kim, Cheol-Hyun; Lee, Byung-Cheol; Jung, Jeeyoun
Abstract : Background: Hyperlipidemia, the most common form of dyslipidemia, is associated with an increased risk of atherosclerotic cardiovascular diseases. There is a constant demand for therapeutic agents with relatively few side effects that can be administered from the initial stage of hyperlipidemia, herbal medicines derived from natural products can be considered candidates for treating dyslipidemia. This study aims to explore the feasibility, preliminary effectiveness, and safety of Gyejibongnyeong-Hwan (GBH) in patients with hyperlipidemia. Methods: This was a 2-armed, parallel, multicenter, and exploratory randomized controlled trial on dyslipidemia. We will recruit 90 patients aged 20 to 65 years with hyperlipidemia between November 2021 and December 2022. Eligible participants will be randomly assigned to receive GBH or placebo granules for 8 weeks and followed up for 4 weeks after 4 weeks of lifestyle modification. The primary outcome is the percentage changes in low-density lipoprotein cholesterol from baseline to week 8. The secondary outcomes are percentage changes in other blood lipid parameters, blood glucose parameters, and blood stasis scores. As an exploratory outcome measure, metabolite analysis will be conducted to observe changes in metabolic patterns. Discussion: This is the first randomized controlled trial to explore the clinical effect and safety of GBH compared to placebo control in patients with hyperlipidemia, thereby potentially facilitating better management of hyperlipidemia. The results of this pilot study could form a foundation for future large-scale confirmatory clinical trials. Ethics and dissemination: This study was permitted by the Ministry of Food and Drug Safety on investigational new drug application on August 12, 2021 and approved by the Institutional Review Board of Kyung Hee University, Seoul, Republic of Korea (KOMCIRB202110012001) on November 26, 2021. The results will be published in a peer-reviewed journal and disseminated electronically and in print.